Polystyrene nanoplastics disrupt mouse placenta development in a sex-dependent manner - Hanin Alahmadi; Allison Harbolic; Christopher De Oliveira-Cordova; Raulle Reynolds; Michelle Jojy; Courtney Potts; Sofia Doan; Tanvi Mathur; Mohammad Saiful Islam; Melisa J. Andrade; Quinton Smith; Phoebe A. Stapleton; et al. (Reproductive Toxicology, 2026)

Effects of adding plant-based menu options on meat selection frequency: A randomized controlled experiment - Jessica E. Hope; Seth A. Green; Jacob R. Peacock; Maya B. Mathur (Food Quality and Preference, 2026)

Decoding of physiological and molecular mechanisms for breeding of drought tolerant crops - Ratnakumar Pasala; Brij Bihari Pandey; ChLN Manikanta; Arun K. Shanker; K. Ramesh; Subramaniam Geethanjali; Amaranatha R. Vennapusa; Kalpalatha Melmaiee; Pooja Srivastava; Amber Gupta; Yogeshwar Singh; Sanket J. More; et al. (Plant Physiology Reports, 2025)

Development of a Power Operated Fenugreek Thresher - C. Naveen Kumar; R. K. Rathod; T. Nageshkumar; S. M. Mathur (Agricultural Research, 2025)

BRCAIndica: a resource for ACMG/AMP classified BRCA1 and BRCA2 variants - Aastha Vatsyayan; R. I. Anu; Prerika Mathur; Divya Uchil; Ashish Joshi; Aradhana Dwivedi; Bhawna Sirohi; Aju Mathew; Dileep Damodaran; Soumya Surath Panda; Spoorthy Kolluri; Shaji K. Ayillath; et al. (Familial Cancer, 2025)

Canonical WNT/β-catenin signaling upregulates aerobic glycolysis in diverse cancer types - Meetu Rathee; Sheikh Mohammad Umar; Arundhathi J.R. Dev; Akanksha Kashyap; Sandeep R. Mathur; Ajay Gogia; Purusottam Mohapatra; Chandra Prakash Prasad (Molecular Biology Reports, 2024)

S17-02: The Long-term Impact of Perinatal Exposures on Susceptibility to Immune-mediated Diseases - K.A. Rychlik; E.J. Illingworth; S.E. Attreed; S.S. Sanchez; A. Grant-Alfieri; M.C. Rodriguez Steube; A. Mathur; I.F. Sanchez; C. Tang; M. Suresh; G. Lopez-Cecetaite; P. Sadhukhan; et al. (Toxicology Letters, 2023)

Mutation spectrum and enzyme profiling of G6PD deficiency in neonates of north India: a prospective study - Upasana Bhattacharyya; Preeti Deswal; Sunil Kumar Polipalli; Diksha Sharma; Manpreet Kaur; Madhulika Kabra; Neerja Gupta; Ramesh Agarwal; A. K. Deorari; V. K. Paul; Shevendru Roy; R. K. Sanjeev; et al. (Journal of Genetics, 2023)

Plastome characterization of Musa indandamanensis, an endemic banana in Andaman and Nicobar Islands, India - Satish Maurya; Vitthal T. Barvkar; Ritesh K. Choudhary; Lalji Singh; Mayank D. Dwivedi; Mudavath C. Naik; Gautam A. Ekka; Manish Kandwal; Roshni R. Mathur; Arun K. Pandey (The Nucleus, 2023)

A novel QTL linked to asparagine synthetase gene for stem height increment in oil palm (E. guineensis Jacq.) identified and validated through integrated genomic approaches - B. Kalyana Babu; R. K. Mathur; G. Ravichandran; P. Anitha; H. P. Bhagya; M. V. B. Venu (Euphytica, 2023)

Investigation of metasomatism using Cu, Zn and Fe stable isotopes: Rodingitization of mafic and ultramafic rocks in ophiolites from northern Greece - N. Zaronikola; V. Debaille; A. Rogkala; P. Petrounias; R. Mathur; S. Decrée; P. Pomonis; K. Hatzipanagiotou; B. Tsikouras (Lithos, 2023)

Cu isotopes in groundwater for hydrogeochemical mineral exploration: A case study using the world-class Mount Isa Cu–Pb–Zn deposit (Australia) - B. Mahan; R. Mathur; I. Sanislav; P. Rea; P. Dirks (Applied Geochemistry, 2023)

The long‐standing significance of genetic diversity in conservation - J. Andrew DeWoody; Avril M. Harder; Samarth Mathur; Janna R. Willoughby (Molecular Ecology, 2021)
Since allozymes were first used to assess genetic diversity in the 1960s and 1970s, biologists have attempted to characterize gene pools and conserve the diversity observed in domestic crops, livestock, zoos and (more recently) natural populations. Recently, some authors have claimed that the importance of genetic diversity in conservation biology has been greatly overstated. Here, we argue that a voluminous literature indicates otherwise. We address four main points made by detractors of genetic diversity's role in conservation by using published literature to firmly establish that genetic diversity is intimately tied to evolutionary fitness, and that the associated demographic consequences are of paramount importance to many conservation efforts. We think that responsible management in the Anthropocene should, whenever possible, include the conservation of ecosystems, communities, populations and individuals, and their underlying genetic diversity.

Metabolic changes in triple negative breast cancer-focus on aerobic glycolysis - J. R. Dev Arundhathi; Sandeep R Mathur; Ajay Gogia; S. V. S. Deo; Purusottam Mohapatra; Chandra Prakash Prasad (Molecular Biology Reports, 2021)

Phenomics, genomics of oil palm (Elaeis guineensis Jacq.): way forward for making sustainable and high yielding quality oil palm - B. Kalyana Babu; R. K. Mathur; P. Anitha; G. Ravichandran; H. P. Bhagya (Physiology and Molecular Biology of Plants, 2021)

Sulfur isotopic characteristics of the Zhaxikang Sb–Pb–Zn–Ag deposit in southern Tibet - D. Wang; Y. Zheng; R. Mathur; H. Ren (Australian Journal of Earth Sciences, 2021)

Analysis of Multimerin 1 (MMRN1) expression in ovarian cancer - Abhinav Saini; Kumari Binita Chandra; Vikrant Kumar; Sandeep R Mathur; J B Sharma; Sunesh Kumar; Savita Yadav (Molecular Biology Reports, 2020)

Identification of QTLs in oil palm (Elaeis guineensis Jacq.) using SSR markers through association mapping - H. P. Bhagya; B. Kalyana Babu; P. M. Gangadharappa; Mahantesha B. N. Naika; D. Satish; R. K. Mathur (Journal of Genetics, 2020)

Comparing transformation pathways across major economies - R. Schaeffer; A. Köberle; H. L. van Soest; C. Bertram; G. Luderer; K. Riahi; V. Krey; D. P. van Vuuren; E. Kriegler; S. Fujimori; W. Chen; C. He; et al. (Climatic Change, 2020)

Development of pepper vein banding virus chimeric virus-like particles for potential diagnostic and therapeutic applications - Pallavi Sabharwal; C. Sushmitha; C. K. Amritha; Usha Natraj; Mathur R. N. Murthy; Handanahal S. Savithri (Archives of Virology, 2020)

Genome-wide association study (GWAS) for stem height increment in oil palm (Elaeis guineensis) germplasm using SNP markers - B. Kalyana Babu; R. K. Mathur; G. Ravichandran; M. V. B. Venu (Tree Genetics & Genomes, 2019)

Day-1 INSAT-3DR Vicarious Calibration Using Reflectance-Based Approach Over Great Rann of Kutch - Piyushkumar N. Patel; K. N. Babu; R. P. Prajapati; Vikram Sitapara; A. K. Mathur (Journal of the Indian Society of Remote Sensing, 2018)

Erratum to: Linear Analysis of Autonomic Activity and Its Correlation with Creatine Kinase-MB in Overt Thyroid Dysfunctions - Manisha Mavai; Yogendra Raj Singh; R. C. Gupta; Sandeep K. Mathur; Bharti Bhandari (Indian Journal of Clinical Biochemistry, 2018)

Linear Analysis of Autonomic Activity and Its Correlation with Creatine Kinase-MB in Overt Thyroid Dysfunctions - Manisha Mavai; Yogendra Raj Singh; R. C. Gupta; Sandeep K. Mathur; Bharti Bhandari (Indian Journal of Clinical Biochemistry, 2018)

Aegle marmelos differentially affects hepatic markers of glycolysis, insulin signalling pathway, hypoxia, and inflammation in HepG2 cells grown in fructose versus glucose-rich environment - H. Aggarwal; J. Nair; P. Sharma; R. Sehgal; U. Naeem; P. Rajora; R. Mathur (Molecular and Cellular Biochemistry, 2018)

Potential of Crop Residue and Fertilizer on Enrichment of Carbon Pools in Upland Soils of Subtropical India - P. K. Ghosh; K. K. Hazra; M. S. Venkatesh; K. K. Singh; Narendra Kumar; R. S. Mathur (Agricultural Research, 2016)

Decay Mechanisms of Near-Inertial Mixed Layer Oscillations in the Bay of Bengal - Shaun Johnston; Dipanjan Chaudhuri; Manikandan Mathur; Daniel Rudnick; Debasis Sengupta; Harper Simmons; Amit Tandon; R. Venkatesan (Oceanography, 2016)

Stage-specific reprogramming of gene expression characterizes Lr48-mediated adult plant leaf rust resistance in wheat - Raman Dhariwal; Vijay Gahlaut; Bhaganagare R. Govindraj; Dharmendra Singh; Saloni Mathur; Shailendra Vyas; Rajib Bandopadhyay; Jitendra Paul Khurana; Akhilesh Kumar Tyagi; Kumble Vinod Prabhu; Kunal Mukhopadhyay; Harindra Singh Balyan; et al. (Functional & Integrative Genomics, 2015)

Monitoring hospital wastewaters for their probable genotoxicity and mutagenicity - Pratibha Sharma; N. Mathur; A. Singh; M. Sogani; P. Bhatnagar; R. Atri; S. Pareek (Environmental Monitoring and Assessment, 2015)

28-Homobrassinolide: a novel oxysterol transactivating LXR gene expression - R. Premalatha; K. Srikumar; D. Vijayalaksmi; G. N. Kumar; P. P. Mathur (Molecular Biology Reports, 2014)

The N-terminal region containing the zinc finger domain of tobacco streak virus coat protein is essential for the formation of virus-like particles - Chhavi Mathur; Kalyani Mohan; T. R. Usha Rani; M. Krishna Reddy; Handanahal S. Savithri (Archives of Virology, 2014)

A new scenario framework for climate change research: the concept of shared socioeconomic pathways - Brian C. O’Neill; Elmar Kriegler; Keywan Riahi; Kristie L. Ebi; Stephane Hallegatte; Timothy R. Carter; Ritu Mathur; Detlef P. van Vuuren (Climatic Change, 2014)

A new scenario framework for Climate Change Research: scenario matrix architecture - Detlef P. van Vuuren; Elmar Kriegler; Brian C. O’Neill; Kristie L. Ebi; Keywan Riahi; Timothy R. Carter; Jae Edmonds; Stephane Hallegatte; Tom Kram; Ritu Mathur; Harald Winkler (Climatic Change, 2014)
This paper describes the scenario matrix architecture that underlies a framework for developing new scenarios for climate change research. The matrix architecture facilitates addressing key questions related to current climate research and policy-making: identifying the effectiveness of different adaptation and mitigation strategies (in terms of their costs, risks and other consequences) and the possible trade-offs and synergies. The two main axes of the matrix are: 1) the level of radiative forcing of the climate system (as characterised by the representative concentration pathways) and 2) a set of alternative plausible trajectories of future global development (described as shared socio-economic pathways). The matrix can be used to guide scenario development at different scales. It can also be used as a heuristic tool for classifying new and existing scenarios for assessment. Key elements of the architecture, in particular the shared socio-economic pathways and shared policy assumptions (devices for incorporating explicit mitigation and adaptation policies), are elaborated in other papers in this special issue.

A new scenario framework for climate change research: background, process, and future directions - Kristie L. Ebi; Stephane Hallegatte; Tom Kram; Nigel W. Arnell; Timothy R. Carter; Jae Edmonds; Elmar Kriegler; Ritu Mathur; Brian C. O’Neill; Keywan Riahi; Harald Winkler; Detlef P. Van Vuuren; et al. (Climatic Change, 2014)
The scientific community is developing new global, regional, and sectoral scenarios to facilitate interdisciplinary research and assessment to explore the range of possible future climates and related physical changes that could pose risks to human and natural systems; how these changes could interact with social, economic, and environmental development pathways; the degree to which mitigation and adaptation policies can avoid and reduce risks; the costs and benefits of various policy mixes; and the relationship of future climate change adaptation and mitigation policy responses with sustainable development. This paper provides the background to and process of developing the conceptual framework for these scenarios, as described in the three subsequent papers in this Special Issue (Van Vuuren et al., 2013; O’Neill et al., 2013; Kriegler et al., Submitted for publication in this special issue). The paper also discusses research needs to further develop, apply, and revise this framework in an iterative and open-ended process. A key goal of the framework design and its future development is to facilitate the collaboration of climate change researchers from a broad range of perspectives and disciplines to develop policy- and decision-relevant scenarios and explore the challenges and opportunities human and natural systems could face with additional climate change.

An ecogenomic analysis of herbivore‐induced plant volatiles in B rassica juncea - Vartika Mathur; Tom O. G. Tytgat; Cornelis A. Hordijk; Harry R. Harhangi; Jeroen J. Jansen; A. Sankara Reddy; Jeffrey A. Harvey; Louise E. M. Vet; Nicole M. van Dam (Molecular Ecology, 2013)
Upon herbivore feeding, plants emit complex bouquets of induced volatiles that may repel insect herbivores as well as attract parasitoids or predators. Due to differences in the temporal dynamics of individual components, the composition of the herbivore‐induced plant volatile ( HIPV ) blend changes with time. Consequently, the response of insects associated with plants is not constant either. Using Brassica juncea as the model plant and generalist Spodoptera spp. larvae as the inducing herbivore, we investigated herbivore and parasitoid preference as well as the molecular mechanisms behind the temporal dynamics in HIPV emissions at 24, 48 and 72 h after damage. In choice tests, Spodoptera litura moth preferred undamaged plants, whereas its parasitoid Cotesia marginiventris favoured plants induced for 48 h. In contrast, the specialist Plutella xylostella and its parasitoid C. vestalis preferred plants induced for 72 h. These preferences matched the dynamic changes in HIPV blends over time. Gene expression analysis suggested that the induced response after Spodoptera feeding is mainly controlled by the jasmonic acid pathway in both damaged and systemic leaves. Several genes involved in sulphide and green leaf volatile synthesis were clearly up‐regulated. This study thus shows that HIPV blends vary considerably over a short period of time, and these changes are actively regulated at the gene expression level. Moreover, temporal changes in HIPV s elicit differential preferences of herbivores and their natural enemies. We argue that the temporal dynamics of HIPV s may play a key role in shaping the response of insects associated with plants.

Obesity and Abdominal Adiposity in Diabetic Dyslipidemia - Manisha Sankhla; Keerti Mathur; Jai Singh Rathor; Sushila Gahlot; R. P. Agrawal (Indian Journal of Clinical Biochemistry, 2011)

Yellowstone Lake: high‐energy geochemistry and rich bacterial diversity - Scott Clingenpeel; Richard E. Macur; Jinjun Kan; William P. Inskeep; Dave Lovalvo; John Varley; Eric Mathur; Kenneth Nealson; Yuri Gorby; Hongchen Jiang; Toben LaFracois; Timothy R. McDermott (Environmental Microbiology, 2011)
Summary Yellowstone Lake is central to the balanced functioning of the Yellowstone ecosystem, yet little is known about the microbial component of its food chain. A remotely operated vehicle provided video documentation ( http://www.tbi.montana.edu/media/videos/ ) and allowed sampling of dilute surface zone waters and enriched lake floor hydrothermal vent fluids. Vent emissions contained substantial H 2 S, CH 4 , CO 2 and H 2 , although CH 4 and H 2 levels were also significant throughout the lake. Pyrosequencing and near full‐length sequencing of Bacteria 16S rRNA gene diversity associated with two vents and two surface water environments demonstrated that this lake contains significant bacterial diversity. Biomass was size‐fractionated by sequentially filtering through 20‐µm‐, 3.0‐µm‐, 0.8‐µm‐ and 0.1‐µm‐pore‐size filters, with the > 0.1 to Acidobacteria , Actinobacteria , Bacteroidetes , α‐ and β‐ Proteobacteria and Cyanobacteria , with 21 other phyla represented at varying levels. Surface waters were dominated by two phylotypes: the Actinobacteria freshwater ac I group and an α‐ Proteobacteria clade tightly linked with freshwater SAR11‐like organisms. We also obtained evidence of novel thermophiles and recovered Prochlorococcus phylotypes (97–100% identity) in one near surface photic zone region of the lake. The combined geochemical and microbial analyses suggest that the foundation of this lake's food chain is not simple. Phototrophy presumably is an important driver of primary productivity in photic zone waters; however, chemosynthetic hydrogenotrophy and methanotrophy are likely important components of the lake's food chain.

Bioremediation of Pulp and Paper Mill Effluent by Tannic Acid Degrading Enterobacter sp. - Yogendra Prakash Singh; Purnima Dhall; R. M. Mathur; R. K. Jain; Vasanta vadde Thakur; Virendra Kumar; Rita Kumar; Anil Kumar (Water, Air, & Soil Pollution, 2011)

Atmospheric correction for sea surface temperature retrieval from single thermal channel radiometer data onboard Kalpana satellite - NAVEEN R SHAHI; NEERAJ AGARWAL; ALOKE K MATHUR; ABHIJIT SARKAR (Journal of Earth System Science, 2011)

Initiation of Locomotion in Decerebrate Cats by Pulsed Magnetic Fields Projected onto Spinal Cord Segments - V. D. Avelev; R. Mathur; D. Behari; N. A. Shcherbakova; I. Yu. Dorofeev; A. A. Savokhin; Yu. P. Gerasimenko (Neuroscience and Behavioral Physiology, 2011)

Identification of quantitative trait loci associated with resistance to foliar diseases in sorghum [Sorghum bicolor (L.) Moench] - S. Murali Mohan; R. Madhusudhana; K. Mathur; D. V. N. Chakravarthi; Sanjay Rathore; R. Nagaraja Reddy; K. Satish; G. Srinivas; N. Sarada Mani; N. Seetharama (Euphytica, 2010)

Variation of Mo isotopes from molybdenite in high-temperature hydrothermal ore deposits - Ryan Mathur; S. Brantley; A. Anbar; F. Munizaga; V. Maksaev; R. Newberry; J. Vervoort; G. Hart (Mineralium Deposita, 2010)

CD38/Cyclic ADP-Ribose Regulates Astrocyte Calcium Signaling: Implications for Neuroinflammation and HIV-1-Associated Dementia - Sugato Banerjee; Timothy F. Walseth; Kathleen Borgmann; Li Wu; Keshore R. Bidasee; Mathur S. Kannan; Anuja Ghorpade (Journal of Neuroimmune Pharmacology, 2008)

Assessment and rationalization of genetic diversity of Papua New Guinea taro (Colocasia esculenta) using SSR DNA fingerprinting - D. Singh; E. S. Mace; I. D. Godwin; P. N. Mathur; T. Okpul; M. Taylor; D. Hunter; R. Kambuou; V. Ramanatha Rao; G. Jackson (Genetic Resources and Crop Evolution, 2008)

Fluid inclusion and Re–Os isotopic evidence for hot, Cenozoic mineralization in the central Pennsylvanian Valley and Ridge Province - R. Mathur; L. Mutti; F. Barra; D. Gold; R. C. Smith; A. Doden; T. Detrie; J. Ruiz; A. McWilliams (Mineralogy and Petrology, 2008)

Stress-inducible expression of At DREB1A in transgenic peanut (Arachis hypogaea L.) increases transpiration efficiency under water-limiting conditions - Pooja Bhatnagar-Mathur; M. Jyostna Devi; D. Srinivas Reddy; M. Lavanya; Vincent Vadez; R. Serraj; K. Yamaguchi-Shinozaki; Kiran K. Sharma (Plant Cell Reports, 2007)

A study of air–sea interaction following the tsunami of 26 December 2004 in the eastern Indian Ocean - V. K. Agarwal; A. Mathur; R. Sharma; N. Agarwal; A. Parekh (International Journal of Remote Sensing, 2007)

Preventive and Curative Biological Treatments for Control of Botrytis cinerea Stem Canker of Greenhouse Tomatoes - R. S. Utkhede; S. Mathur (BioControl, 2006)

Qualitative and quantitative analysis of snow parameters using passive microwave remote sensing - V. D. Mishra; P. Mathur; R. P. Singh (Journal of the Indian Society of Remote Sensing, 2005)

Genotyping of urinary and fecal Proteus mirabilis isolates from individuals with long-term urinary catheters - S. Mathur; N. A. Sabbuba; M. T. E. Suller; D. J. Stickler; R. C. L. Feneley (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Sub-Surface Investigations on Deep Saline Groundwater of Charnockite Rock Formation, Kalpakkam, India - C. Gurumoorthy; P. Sasidhar; V. Arumugham; R. K. Mathur (Environmental Monitoring and Assessment, 2004)

Toxic Effects of Textile Printing Industry Effluents on Liver and Testes of Albino Rats - R. Krishnatrey; S. Sharma; K. P. Sharma; N. Mathur (Bulletin of Environmental Contamination and Toxicology, 2003)

Regulation of cell expansion by the DISTORTED genes in Arabidopsis thaliana: actin controls the spatial organization of microtubules - B. Schwab; J. Mathur; R. R. Saedler; H. Schwarz; B. Frey; C. Scheidegger; M. Hülskamp (Molecular Genetics and Genomics, 2003)

Changes in Brain Intracellular pH and Membrane Phospholipids on Oxygen Therapy in Hypoxic Patients with Chronic Obstructive Pulmonary Disease - G. Hamilton; R. Mathur; J.M. Allsop; D.M. Forton; N.S. Dhanjal; R.J. Shaw; S.D. Taylor-Robinson (Metabolic Brain Disease, 2003)

Intercomparison of IRS-P4-MSMR derived geophysical products with DMSP-SSM/I and TRMM-TMI finished products - A. K. Varma; R. M. Gairola; A. K. Mathur; B. S. Gohil; Vijay K. Agarwal (Journal of Earth System Science, 2002)

Rain rate measurements over global oceans from IRS-P4 MSMR - A. K. Varma; R. M. Gairola; Samir Pokhrel; B. S. Gohil; A. K. Mathur; Vijay K. Agarwal (Journal of Earth System Science, 2002)

Age and sources of the ore at Tharsis and Rio Tinto, Iberian Pyrite Belt, from Re-Os isotopes - R. Mathur; J. Ruiz; F. Tornos (Mineralium Deposita, 1999)

In vitro plantlet regeneration from mature zygotic embryos of Pinus wallichiana A.B. Jacks - G. Mathur; R. Nadgauda (Plant Cell Reports, 1999)

Polychlorinated Dibenzo-p-Dioxins and Dibenzofurans in Storm Water Outfalls Adjacent to Urban Areas and Petroleum Refineries in San Francisco Bay, California - R. J. Wenning; D. B. Mathur; D. J. Paustenbach; M. J. Stephenson; S. Folwarkow; W. J. Luksemburg (Archives of Environmental Contamination and Toxicology, 1999)

Isolation of two antifungal compounds fromNeolitsea cuipala and their activity against some plant pathogenic fungi - P. Boruah; P. Deka Bhuyan; S. C. Dutta; S. Mohan; R. K. Mathur (Folia Microbiologica, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Effects of atmospheric boundary layer mixing representations on vertical distribution of passive and reactive tracers - K. Alapaty; R. Mathur (Meteorology and Atmospheric Physics, 1998)